Estruturação funcional do zooplâncton no espaço e no tempo em uma planície de inundação neotropical. - Braghin, Louizi de Souza Magalhães (2019)
Freshwater ecosystems provide many services to society directly related to species functions. Spatial and temporal variations on community structure may occur naturally due to environmental heterogeneity and seasonal disturbances or as consequence of anthropic changes. In freshwater systems, zooplankton is a link between primary producers and others trophic levels, contributing to ecosystem productivity and nutrients cycling. At spatial scale, we investigated the distribution pattern of species functional traits, distribution pattern of functionally redundant species (similar functional traits) and functionally rare species (distinct functional traits) among watersheds (landscape scale) and among habitats with different spatial configuration (habitat type scale). We evaluated functional species traits distribution, rarity and redundancy indexes in 36 habitats in the Upper Paraná River floodplain in 2000, 2001, 2010 and 2011, using a measure of individuals proportion estimated for each categorical trait and combination of these traits. In general, heterogeneity among habitat types was more important to structure functional zooplankton than differences on environmental conditions among watersheds. However, differences at watershed scale were important on functionally rare species distribution. Our findings suggest that heterogeneous environmental configuration among habitat types is important to structure all community, but keeping the pristine features of watersheds free of dams may contribute to conservation of functionally rare species. We also investigated temporal tendencies on zooplankton temporal richness (FRic), functional equitability (FEve) and functional divergence (FDiv) in 12 habitats along 16 monitoring years (2000-2016), and their relationships to environmental predictors (chlorophyll-a, depth and turbidity). We tested temporal tendencies and the relationships to predictors using Generalized Additive Models (GAM). FRic and FEve fluctuated cyclically and opposite to each other every five years of study, with the highest FRic values occurring simultaneously with the lowest FEve values. FDiv presented trends similar to Fric, but FDiv only declined between 2005 and 2010. All functional diversity indexes were better explained by temporal variation, depth and chlorophyll-a concentration. However, the influence of each predictor was different for each component of diversity. These variations corresponded to extreme floods and prolonged drought periods. This implies that the maintenance of regular periods of flood and drought can contribute to the conservation of the functional diversity in the floodplain and, consequently, to the resilience of this ecosystem. So, preserve the floodplain spatial and temporal configuration is important to sustain the original functional state of this ecosystem.